2020
DOI: 10.1200/jop.19.00736
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Forgone Medical Care Among Cancer Survivors

Abstract: PURPOSE: Financial hardship is increasingly understood as a negative consequence of cancer and its treatment. As patients with cancer face financial challenges, they may be forced to make a trade-off between food and medical care. We characterized food insecurity and its relationship to treatment adherence in a population-based sample of cancer survivors. METHODS: Individuals 21 to 64 years old, diagnosed between 2008 and 2016 with stage I-III breast, colorectal, or prostate cancer were identified from the New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 38 publications
3
34
2
Order By: Relevance
“…In the context of cancer care, several previous studies have estimated the prevalence of food insecurity and described interventions to improve food insecurity. Our estimate that 14.8% of African American cancer survivors in Detroit experience food insecurity is similar to an estimate from Simmons et al, 32 who reported that 17.4% of patients approached in waiting rooms of a university cancer center experienced food insecurity, but lower than estimates among underserved oncology patients in New York City (56% food insecure) 33 or population‐based cancer survivors in New Mexico (36% food insecure) 34 . Differences in measures of food insecurity and in populations included, particularly with respect to socioeconomic factors, food environments, and access to social programs designed to increase food security, likely contribute to these differences in estimates.…”
Section: Discussionsupporting
confidence: 86%
“…In the context of cancer care, several previous studies have estimated the prevalence of food insecurity and described interventions to improve food insecurity. Our estimate that 14.8% of African American cancer survivors in Detroit experience food insecurity is similar to an estimate from Simmons et al, 32 who reported that 17.4% of patients approached in waiting rooms of a university cancer center experienced food insecurity, but lower than estimates among underserved oncology patients in New York City (56% food insecure) 33 or population‐based cancer survivors in New Mexico (36% food insecure) 34 . Differences in measures of food insecurity and in populations included, particularly with respect to socioeconomic factors, food environments, and access to social programs designed to increase food security, likely contribute to these differences in estimates.…”
Section: Discussionsupporting
confidence: 86%
“…The present ndings align with the existing research suggesting that food insecurity negatively impacts health services access and utilization among US residents. The existing literature suggests that food insecurity is associated with delaying medical care [37], lower treatment adherence [38,39], and poor chronic disease management [18,40]. Berkowitz and colleagues in 2014 attributed these trends to the 'treat or eat' dilemma experienced by food-insecure people; in such instances, they are forced to choose between accessing medical services or meeting the basic needs of food and shelter [41].…”
Section: Discussionmentioning
confidence: 99%
“…FI is prevalent in the United States and a strong mediator of disparities in cancer mortality (49). Although many patients will be food insecure prior to their diagnosis of a digestive cancer, cancer is financially costly to treat and could place individuals at risk of becoming food insecure (14,20). Even patients with commercial insurance are at risk of the detrimental financial impact of cancer care due to increasing out-of-pocket costs (15).…”
Section: Discussionmentioning
confidence: 99%
“…The additional burden of cancer care (e.g., treatment costs, missed days of work) can lead many survivors vulnerable to developing unmet health-related social needs, such as FI. (20,22). Also, individuals living in food insecure households are more likely to consume low-cost, high-calorie dense foods, smoke, and delay preventative care (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation